Abnormal white matter correlates with neuropsychological impairment in children with localization‐related epilepsy. (7th May 2013) - Widjaja, Elysa; Skocic, Jovanka; Go, Cristina; Snead, O. Carter; Mabbott, Donald; Smith, Mary Lou
Summary Purpose The white matter (WM) is considered critical for linking cortical processing networks necessary for cognition. The aim of this study was to assess diffusion tensor imaging (DTI) measures of regional WM in children with nonlesional localization‐related epilepsy in comparison to controls, and to determine the relation between lobar WM and neuropsychological performance. Methods Forty children with nonlesional localization‐related epilepsy and 25 healthy controls with no neurological or psychiatric disorders and normal magnetic resonance imaging (MRI) were recruited. All patients and controls underwent neuropsychological testing that evaluated intelligence, language, memory, executive function, and motor function, as well as DTI to assess regional WM measures of fractional anisotropy (FA) and mean diffusivity (MD). The regional FA and MD were compared between patients and controls, and correlated with neuropsychological function. The relations between regional FA and MD with age at seizure onset and duration of epilepsy were assessed. Key Findings Twenty‐one patients had left‐sided and 19 patients had right‐sided epilepsy. There were no significant differences in seizure‐related variables including age at seizure onset, duration of epilepsy, seizure frequency, and number of antiepileptic medications, as well as no significant differences in neuropsychological function and DTI measures of white matter in left‐sided compared to right‐sided epilepsy. Therefore, all the patients with epilepsy were treated as one group. Patients with epilepsy performed significantly worse on intelligence (p < 0.001), language (p < 0.001), and executive function (p = 0.001) evaluation than controls. Patients had significantly reduced FA in left frontal (p = 0.015), right frontal (p = 0.004), left temporal (p = 0.039), right temporal (p = 0.003), right parietal (p = 0.014), and right occipital (p = 0.025) WM relative to controls. There were no significant regional WM differences (all p > 0.05) in MD between patients and controls. There was a significant positive correlation between right temporal FA with language (r = 0.535, p < 0.001) and executive function (r = 0.617, p < 0.001), as well as between body of corpus callosum FA with intelligence (r = 0.536, p < 0.001) and language (r = 0.529, p < 0.001) in patients. Left parietal MD was significantly correlated with language (r = −0.545, p < 0.001) in patients. FA of right temporal WM was significantly associated with age at seizure onset (t = 4.97, p < 0.001). Significance There was widespread regional WM abnormality in children with nonlesional localization‐related epilepsy, which was associated with impaired neuropsychological function. The impairment in WM may reflect disruption in the connectivity for cortical processing networks, which is necessary for the development of cognition.